PROHIBITION OF NOTARY TO CREATE A DEED OF TRANSFER OF RIGHTS RELATED TO FAMILY RELATIONS - Hendrawan Hendrawan; Annalisa Annalisa; Abdullah Abdullah (Warmadewa Press, 2025)
Notaries are public officials who are authorized to make authentic deeds, but notaries have limited authority, namely they are not allowed to make deeds for themselves, their wives/husbands, or other people who have family ties with the notary either by marriage or blood relations in the lineage. The prohibition on notaries to make deeds of transfer of rights related to family relations is discussed normatively in this study, where notaries commit violations by making deeds of transfer of rights for parties who have family ties with the notary. This study aims to analyze the position and legal consequences of making deeds of transfer of rights by notaries related to family relations, as well as the legal considerations of judges related to deeds of transfer of rights that have family ties with notaries. The results of this study indicate that the position of the deed made by a notary who has a family relationship with the party appearing remains valid, but as a result the deed is no longer an authentic deed but is degraded as a deed under hand, if there is a party who feels aggrieved by the notary, the parties can sue for compensation. The judge does not impose sanctions on notaries who make deeds of transfer of rights related to family relationships.